Vocational High School Teachers’ Efforts in Equipping Graduates with Soft Skills Based on Work Demands - Rudi Nur Syamsudin; Sukardi Sukardi; He Shiyu (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
A preliminary study in Yogyakarta showed that the graduates’ enthusiasm to enter building construction study program in vocational high school was low. One of the factors affecting the graduates’ enthusiasm was related to the low-level teachers’ efforts in preparing the graduates’ soft skills. This study aimed to identify (1) the integration level of soft skills elements, and (2) the teachers' obstacles to equipping the graduates' soft skills. It was descriptive quantitative research conducted in the study program of building construction at vocational high schools. The results of the study showed: (1) the integration level of communicative ability, integration level of cooperative competence, integration level of motivating ability, integration level of developing etiquette and moral, and integration level of building responsibility were wholly integrated. Then, the integration level of problem-solving ability and integration level of science and technology mastery was mostly integrated; (2) the obstacles included: the students’ ignorance attitude, the lack of collaboration between the students’ parents and the school stakeholders in developing the graduates’ soft skills, the absence of soft skills training and the unsupported school culture. Those obstacles impeded the graduates’ soft skills.